Cyst‐theca relationships and phylogenetic positions of Peridiniales (Dinophyceae) with two anterior intercalary plates, with description of Archaeperidinium bailongense sp. nov. and Protoperidinium fuzhouense sp. nov. Issue 2 (1st April 2015) - Liu, Tingting; Mertens, Kenneth Neil; Ribeiro, Sofia; Ellegaard, Marianne; Matsuoka, Kazumi; Gu, Haifeng
Summary: Protoperidinium species with two anterior intercalary plates were originally classified by Jörgensen in the subgenus Archaeperidinium and assigned to the sections Excentrica, Avellana and Archaeperidinium by Taylor, on the basis of the relative size of anterior intercalary plates and the extent of cingulum displacement. Phylogenetic relationships among these three sections have not been fully explored. Recently, Archaeperidinium was reinstated as a genus, but several species fitting the emended description have not been transferred formally as molecular data were not available. In the present study we examined the cyst‐theca relationship of seven species with two anterior intercalary plates: four species assigned to Protoperidinium and three to Archaeperidinium, from the China Sea. Partial large subunit ribosomal DNA sequences were obtained from these seven species by single‐cell polymerase chain reaction, and for the cyst of Protoperidinium stellatum from France. Two new species, Archaeperidinium bailongense and Protoperidinium fuzhouense, were described based on both theca and cyst morphology, and the cyst‐theca relationships of A. constrictum and P. abei var. rotunda were established for the first time. Maximum‐likelihood and Bayesian inference analyses revealed that P. fuzhouense was nested within the Protoperidinium sensu stricto clade despite having only six postcingular plates, and sections Excentrica, Avellana and the genus Archaeperidinium were all monophyletic. Our results suggest that the presence/absence of a sulcal fin and antapical horns and the displacement of the cingulum are the most stable characteristics of the motile stages within the respective clades.